Powdery mildew of plants of the family Crassulaceae in Belarus: taxonomic composition of pathogens and their hosts - Khramtsov, Аlexander K.; Sidorova, Svetlana G. (Experimental Biology and Biotechnology, 2025)
It was established that in Belarus powdery mildew on introduced plants of the family Crassulaceae (Сrassula ovata, Hylotelephium maximum, H. × mottramianum, Kalanchoe blossfeldiana, K. daigremontiana, K. laciniata, Phedimus sp. and Ph. spurius) both when grown in open ground and in year-round indoor cultivation is caused by the alien fungi Erysiphe sedi, Golovinomyces orontii and Pseudoidium kalanchoes. The morphological characteristics of the fungus P. kalanchoes based on the results of studying its samples collected in Belarus are presented for the first time. It was identified that the fungi E. sedi and G. orontii have expanded their range of hosts: three new species of feeding plants of the family Crassulaceae (K. blossfeldiana, K. daigremontiana and Phedimus sp.) were discovered.
Keywords: powdery mildew; Erysiphe; Golovinomyces; Pseudoidium; Crassulaceae; anamorph; teleomorph; host plant; mycobiota; Belarus